Cup and Ring-Markings on Craig Ruenshin, with some Comparative Notes (Proceedings of the Society of Antiquaries of Scotland, 1938)
The larger group of carvings is on a flat piece of living rock. The smaller group is found on a tilted rock face. The larger group comprises twenty cups, nine surrounded\r by circles. One cup is encircled by two concentric rings, a second by three rings, and a third by three rings and a fourth ring only partly discernible. In the last\r case there is a cup in the third ring and another in the remains of the fourth. There are some vestiges of channels from the cups through the circle, but the whole is badly weathered. The smaller group consists of eight cups, twice associated with circle and channel, twice with a circle only, and twice with two circles and a channel which in one instance ends in a cup. These markings are also weathered, but less than in the first group.